ANALISIS NILAI TAMBAH DAN PROFITABILITAS AGROINDUSTRI RUMAH TANGGA ETANOL DI KABUPATEN SUKOHARJO - Hanifah Erma Ratnasari Usada; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2011)
This research aims to: (1) measure thefeasibility rate of agroindustry of ethanol, (2) thefactors that affect valueadded agro-processing of sugar cane molasses into ethanol, (3) thefactors that affect the profit of ethanol agroindustry, (4) the relationship or the mutual influence between the value added to the feasibility of covering the profit, profitability, and break eventpoint (BEP). The research was conducted in Sukoharjo regency in theperiod of November 2009 until October 2010. The results of this research indicate that: (1) the average gain per unit of marketing during the period November 2009 to October 2010 amounting to Rp. 220,311,318.00. and the level of profitability (net B/C ratio) for each agro-processing of molasses into ethanol is 53.91% so it can be seen that the ethanol agroindustry is feasible to develop and deliver benefits for business owners. (2) Factors that significantly influence the value added are: the production capacity, the amount of raw materials, and the amount of fuel. (3) Factors that significantly influence the profit are: the price of sugar cane molasses as the main raw materials, auxiliary input price of caustic soda, and wage labor. (4) The existence of a positive relationship between the value added to profits and profitability, while the relationship between value-added is inverseproportional to the break evenpoint.Penelitian ini bertujuan untuk mengetahui: (1) kelayakan agroindustri keeil etanol, (2) faktor-faktor yang mempengaruhi niJai tambah agroindustri pengolahan tetes tebu menjadi etanol, (3) faktor-faktor yang mempengaruhi keuntungan usaha agroindustri keeil etanol, (4) hubungan atau pengaruh timbal balik antara nilai tambah dengan kelayakan yang meliputi keuntungan, profitabilitas, dan titik impas (BEP). Penelitian dilaksanakan di Kabupaten Sukoharjo pada periode usaha Nopember 2009 sampai dengan Oktober 2010. Hasil penelitian menunjukkan bahwa: (1) Agroindustri etanollayak untuk dikembangkan dan memberikan keuntungan bagi pemilik usahanya. Rata-rata keuntungan per usaha selama periode Nopember 2009 sampai dengan Oktober 2010 sebesar Rp. 220.311.318,00 dan tingkat profitabilitas per usaha agroindustri pengolahan tetes tebu menjadi etanol adalah 53,91%. (2) Faktor-faktor yang berpengaruh signifikan terhadap nilai tambah adalah kapasitas produksi yang dihasilkan, jumlah bahan baku, dan jumlah bahan bakar. (3) Faktor-faktor yang berpengaruh signifikan terhadap keuntungan adalah harga tetes tebu sebagai bahan baku utama, harga input penolong soda api, dan upah tenaga kerja. (4) Adanya hubungan positif antara nilai tambah dengan keuntungan dan profitabilitas, sementara itu hubungan antara nilai tambah berbanding terbalik terhadap titik impas.